Pendidikan Karakter dan Multikultural Sebagai Pembangun Karakter Anak Bangsa di Sekolah Dasar Negeri Banyusari - Kusnaeni, Ulya Nur; Kamila, Aulia Zalwa; Sa'diyah, Chalimatus; Anam, Fahri Syaiful; Rahmawati, Puji (Prosiding University Research Colloquium, 2022)
The purpose of this study was to find out how the application of the habituation method in the formation of multicultural characters in SD Negeri Banyusari and to find out the factors that support and inhibit the formation of the character of students in SD Negeri Banyusari. This research is field research with qualitative research type with source triangulation technique. The data collection method used in this research is the method of observation, interviews, and documentation. The results of the interviews were obtained from the 1st-grade teacher, 4st-grade teacher, and 1 librarian staff. From the results of the analysis carried out, the formation of character and multicultural education of students is carried out by the habituation method at SD Negeri Banyusari which includes: Gratitude, responsibility, discipline, courtesy, friendly, and respect for others. Character education and multiculturalism become an effort to shape the character of the nation's children and so that it can be an effort to unite the next generation who understand here Bhineka Tunggal Ika.To support the implementation of character building and multicultural education in Banyusari Elementary School, character planting is held through printed media in the form of madding which is displayed in front of each class.